Genetic variants in the G gamma-globin promoter modulate fetal hemoglobin expression in the Colombian population (2023)
Fetal hemoglobin (HbF) is a determining factor for the development of sickle cell anemia. High HbF levels lower the intensity of symptoms of this disease. HbF levels can vary in patients with sickle cell anemia and individuals without the disease.